League of Nations and Latin America. Chile facing Peru and Bolivia in the first half of the 20th century (Revista de Estudios Europeos, 2024)
After the 1879 war that pitted Chile against Peru and Bolivia, a complex process of negotiations began that led to the establishment of new border limits and treaties that summarised the steps to be taken in the following years. Over the years, some of the principles established, due to delay or non-compliance, led these countries to expose their situation in the recently created League of Nations (1919). In this study we analyse the positions adopted by Chile, considering the costs and benefits of participating in the international organisation in view of its interests and its relationship with its ‘neighbourhood’. Translated with DeepL.com (free version)
Keywords: League of Nations; International Treaties; Pacific War